Preparation of biodiesel from RBD palm oil via single step transesterification process with the aid of ultrasonic irradiation and (NaOh) as catalyst - Mohd Nasrul, Yaakop (2008)
The world is increasingly accepting the fact that conventional sources of fuel and energy are being rapidly depleted and cannot be renewed. One possible alternative to fossil fuel is biodiesel, biodiesel defined as “a substitute for, or an additive to Diesel fuel that is derived from the oils and fats of plants and animals”. The main advantages of using this alternative fuel are its renewability, better quality of exhaust gas emissions and its biodegradability. Renewable resources as the raw material for production of biodiesel can be categorized into vegetable oils, animal fat and algae and there are at least four ways in which oils and fats can be converted into biodiesel which are direct use and blending, micro-emulsion, pyrolysis (thermal cracking) and transesterification. Transesterification or alcoholysis is the displacement of alcohol from an ester by another, the presence of a catalyst accelerates the conversion. In this project, the RBD palm oil was used as raw material to produce biodiesel via single step transesterification process in the presence of NaOH as homogeneous alkali catalyst and ultrasonic irradiation. This process was studied in order to find the optimal conditions of the process, the experiment plan was involved three independent variables which are catalyst concentration, reaction temperature and reaction time. The first parameter studied was the catalyst concentrations, the optimal could be achieved at catalyst concentration at 0.5 wt%. The second parameter was the reaction temperature, the optimal temperature is 40°C. The last parameter studied was the reaction time and the result showed that the reaction time at 20 minutes was the best optimal value. Overall, after conducting three different set of experiments, it can be concluded that the best condition for biodiesel production are 71.5% methyl ester with 74.01% product yield and 0.02% moisture contents.